Testing the relation between ADHD and hyperfocus experiences - Groen, Yvonne; Priegnitz, Ulrike; Fuermaier, Anselm B. M.; Tucha, Lara; Tucha, Oliver; Aschenbrenner, Steffen; Weisbrod, Matthias; Garcia Pimenta, Miguel (Research in developmental disabilities, 2020)
Background - Attention-deficit/hyperactivity disorder (ADHD) has been associated with hyperfocus, a transient experience of enhanced attentional focus and diminished awareness of time and the environment. - Aims - This study aims to investigate the association between the frequency, duration and pervasiveness of hyperfocus across different situations in adults with and without ADHD. - Method and procedures - Within a healthy sample (n = 1124), we analysed correlations between scores on the ADHD Rating Scale and self-reports of frequency, duration and pervasiveness of hyperfocus. An ADHD patient group (n = 78) was compared to matched healthy participants on all hyperfocus variables. - Outcomes and results - In healthy adults, the frequency of hyperfocus was positively correlated with ADHD traits; older age and higher education were correlated with fewer hyperfocus occurrences in a smaller number of situations. ADHD patients and matched controls did not differ in the occurrence, frequency, duration and pervasiveness of hyperfocus, but hyperfocus was less likely to occur in educational and social situations in ADHD patients. - Conclusions and implications - Hyperfocus experiences are not specific of ADHD patients. The divergent findings might reflect multiple hyperfocus dimensions (situational and motivational) assessed in different studies which need to be addressed in future research.
Gesehen am 09.02.2022